The Effect of Current Ratio, Return on Assets, Debt to Asset Ratio, and Earnings per Share on Stock Prices - Prabowo, Odi; Thalita Sada Abbas, Aulia; Evrilyan, Dwi; Nurwakia, Nurwakia; Hamid Habbe, Abdul; Bandang, Agus (Cita konsultindo, 2026)
This study examines the effect of the Current Ratio, Return on Assets, Debt to Asset Ratio, and Earnings per Share on stock prices of technology sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period. A quantitative approach was employed, with samples selected using purposive sampling, and data were analyzed through multiple linear regression. The results indicate that the Current Ratio does not have a significant effect on stock prices, and Return on Assets also shows no significant influence. In contrast, the Debt to Asset Ratio has a negative and significant effect on stock prices, while Earnings per Share has a positive and significant effect. These findings suggest that investors in the technology sector place greater emphasis on leverage risk and earnings performance than on short-term liquidity and profitability measures.